Nanoimprint Lithography: A Processing Technique for Nanofabrication Advancement - Zhou, Weimin; Min, Guoquan; Zhang, Jing; Liu, Yanbo; Wang, Jinhe; Zhang, Yanping; Sun, Feng (Nano-Micro Letters, 2011)
Nanoimprint lithography (NIL) is an emerging micro/nano-patterning technique, which is a high-resolution, high-throughput and yet simple fabrication process. According to International Technology Roadmap for Semiconductor (ITRS), NIL has emerged as the next generation lithography candidate for the 22 nm and 16 nm technological nodes. In this paper, we present an overview of nanoimprint lithography. The classfication, research focus, critical issues, and the future of nanoimprint lithography are intensively elaborated. A pattern as small as 2.4 nm has been demonstrated. Full-wafer nanoimprint lithography has been completed on a 12-inch wafer. Recently, 12.5 nm pattern resolution through soft molecular scale nanoimprint lithography has been achieved by EV Group, a leading nanoimprint lithography technology supplier.